Carbon Flux Distribution and Kinetics of Cellulose Fermentation in Steady-State Continuous Cultures of Clostridium cellulolyticum on a Chemically Defined Medium - Desvaux, Mickaël (American Society for Microbiology, 2001)
The metabolic characteristics of Clostridium cellulolyticum, a mesophilic cellulolytic nonruminal bacterium, were investigated and characterized kinetically for the fermentation of cellulose by using chemostat culture analysis. Since with C. cellulolyticum (i) the ATP/ADP ratio is lower than 1, (ii) the production of lactate at low specific growth rate (μ) is low, and (iii) there is a decrease of the NADH/NAD(+) ratio and q(NADH produced)/ q(NADH used) ratio as the dilution rate (D) increases in carbon-limited conditions, the chemostats used were cellulose-limited continuously fed cultures. Under all conditions, ethanol and acetate were the main end products of catabolism. There was no shift from an acetate-ethanol fermentation to a lactate-ethanol fermentation as previously observed on cellobiose as μ increased (E. Guedon, S. Payot, M. Desvaux, and H. Petitdemange, J. Bacteriol. 181:3262–3269, 1999). The acetate/ethanol ratio was always higher than 1 but decreased with D. On cellulose, glucose 6-phosphate and glucose 1-phosphate are important branch points since the longer the soluble β-glucan uptake is, the more glucose 1-phosphate will be generated. The proportion of carbon flowing toward phosphoglucomutase remained constant (around 59.0%), while the carbon surplus was dissipated through exopolysaccharide and glycogen synthesis. The percentage of carbon metabolized via pyruvate-ferredoxin oxidoreductase decreased with D. Acetyl coenzyme A was mainly directed toward the acetate formation pathway, which represented a minimum of 27.1% of the carbon substrate. Yet the proportion of carbon directed through biosynthesis (i.e., biomass, extracellular proteins, and free amino acids) and ethanol increased with D, reaching 27.3 and 16.8%, respectively, at 0.083 h(−1). Lactate and extracellular pyruvate remained low, representing up to 1.5 and 0.2%, respectively, of the original carbon uptake. The true growth yield obtained on cellulose was higher, [50.5 g of cells (mol of hexose eq)(−1)] than on cellobiose, a soluble cellodextrin [36.2 g of cells (mol of hexose eq)(−1)]. The rate of cellulose utilization depended on the solid retention time and was first order, with a rate constant of 0.05 h(−1). Compared to cellobiose, substrate hydrolysis by cellulosome when bacteria are grown on cellulose fibers introduces an extra means for regulation of the entering carbon flow. This led to a lower μ, and so metabolism was not as distorted as previously observed with a soluble substrate. From these results, C. cellulolyticum appeared well adapted and even restricted to a cellulolytic lifestyle.